Speckle Suppression Using Cylindrical Self-Diffraction for Cylindrical Phase-Only Hologram - Feng-Ming Jin; Yang Wu; Jun Wang; Chun Chen; Chan-Juan Liu; Yu-Hen Hu (IEEE Photonics Journal)
In the reconstruction of cylindrical phase-only hologram (POH), speckle noise caused by the addition of random phase is rarely discussed. Although some speckle noise suppression algorithms have been proposed for planar POH, it does not work well if they are directly applied to cylindrical POH. To solve this issue, the cylindrical self-diffraction iteration (CSDI) algorithm is proposed. This is an iteration algorithm based on the cylindrical self-diffraction model which is a special case of the cylindrical backward-propagation model at a limit condition. Simulation results show that CSDI can suppress speckle noise and improve the quality of reconstructed images significantly. Furthermore, the proposed CSDI algorithm outperforms conventional algorithms, which work well in planar POH and are directly applied to cylindrical POH, in suppressing speckle noise for cylindrical POH. To our best knowledge, the models of cylindrical backward-propagation and cylindrical self-diffraction as well as the concept of CSDI are firstly proposed and applied to speckle suppression of cylindrical POH.